2021
DOI: 10.1017/ice.2021.119
|View full text |Cite
|
Sign up to set email alerts
|

Multipronged infection control strategy to achieve zero nosocomial coronavirus disease 2019 (COVID-19) cases among Hong Kong healthcare workers in the first 300 days of the pandemic

Abstract: Background: Nosocomial outbreaks leading to healthcare workers (HCWs) infection and death have been increasingly reported during the coronavirus disease 2019 (COVID-19) pandemic. An effective intervention is urgently needed to reduce nosocomial acquisition. Methods: We summarized our experience of multi-pronged infection control (IC) strategy in the first 300 days (December 31, 2019 to October 25, 2020) of COVID-19 era under the governance of Hospital Authority in Hong Kong. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
0
28
1
Order By: Relevance
“…A portable high‐efficiency particulate air (HEPA) filter is placed outside the door during the collection of specimens. Residents tested positive for SARS‐CoV‐2 will be admitted to airborne infection isolation unit in public hospitals or community isolation and treatment facilities to minimize the risk of COVID‐19 outbreak 6,7 …”
mentioning
confidence: 99%
“…A portable high‐efficiency particulate air (HEPA) filter is placed outside the door during the collection of specimens. Residents tested positive for SARS‐CoV‐2 will be admitted to airborne infection isolation unit in public hospitals or community isolation and treatment facilities to minimize the risk of COVID‐19 outbreak 6,7 …”
mentioning
confidence: 99%
“…This includes epidemiological analysis, zoning and cohorting, precise PPE management, and environmental disinfection. Our findings highlighted that immediate practical guidance and intensified training on-site by experts with experience were effective to make all staff familiar with strict IPC measures in hospitals less experienced in NIs, as the Hong Kong study stressed [ 45 ]. Moreover, its study suggested that the on-site simulation drill in normal times was useful [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlighted that immediate practical guidance and intensified training on-site by experts with experience were effective to make all staff familiar with strict IPC measures in hospitals less experienced in NIs, as the Hong Kong study stressed [ 45 ]. Moreover, its study suggested that the on-site simulation drill in normal times was useful [ 45 ]. In Japan, at present, the cluster teams of MOHLW and the infectious disease specialists of DMATs affiliated with each prefecture play an important role in COVID-19 control and training HCWs to deal with on-site outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations